The Influence of Parents on Medication Adherence of Their Children in China: A Cross-Sectional Online Investigation Based on Health Belief Model - Pu Ge; Pu Ge; Pu Ge; Si-tong Liu; Shu-xian Xu; Jin-zi Zhang; Yong-jie Lai; Run-chen Fu; Xin-yu Ke; Xin-yu Ke; Xin-yu Ke; Juan Zhao; et al. (Frontiers Media S.A., 2022)
ObjectiveTo explore the influence of parents on the medication adherence of their children.Study DesignA cross-sectional online investigation.MethodsA questionnaire with 41 questions was designed based on the health belief model (HBM) distributed and collected online in 28 cities around China through multi-stage stratified sampling. The reliability of the questionnaire was assessed with Cronbach's α coefficient and split-half reliability, and its validity was evaluated with exploratory factor analysis and content validity index. The structural equation model (SEM) was constructed to explore the relationship between the parents' health beliefs and their children's medication adherence. Subgroup analysis was conducted to study the differences between parents with different demographic characteristics (male and female, rural and urban).Results573 questionnaires were included for analysis, with an effective rate of 62.97%. The Cronbach'α coefficient of the questionnaire was 0.821 > 0.6, the split-half reliability was 0.651 > 0.6, the I-CVI of each dimension were >0.78, and the S-CVI/AVE (I-CVI average) was 0.95 > 0.9. The result of the questionnaire exploratory factor analysis met the standard. According to the SEM, self-efficacy (λ = 0.177), perceived susceptibility (λ = −0.244), and perceived severity (λ = 0.243) were direct influencing factors of children's medication adherence. In the subgroup analysis, the model established by each subgroup was consistent with the model established by the overall sample. The absolute values of females' perceived susceptibility, severity, and self-efficacy for their children's medication adherence path coefficients were higher than males'.ConclusionParents' perceived severity and self-efficacy may positively impact on their children's medication adherence, while parents' susceptibility to children's medication non-adherence may negatively impact on children's medication adherence. Objective constraints, perceived barriers, and benefits may in directly impact on children's medication adherence. Women's health beliefs appear to have a more significant impact on their children's medication adherence than men's. It may be an effective strategy to increase their children's medication adherence by improving parents' health beliefs. Medical staff should explain medication adherence knowledge to the parents of children, and inform the children of the possible consequences of non-adherence with medication, to improve the subjective perception of parents on the severity of children's non-adherence with medication, and improve parents' self-efficacy in rational medication for children. In addition, attention should be paid to the mental health of the parents, and more social and psychological support.